1982
DOI: 10.1136/hrt.48.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of ductus arteriosus with left to right shunt in the older patient.

Abstract: SUMMARY Eight hundred and four patients with persistence of the ductus arteriosus were seen in Edinburgh between 1940 and 1979. Thirty-seven of them reached the age of 50 years, and in 32 the shunt was exclusively from left to right. Fifteen of the 32 were subsequently treated surgically.None of the 32 was lost to follow-up. Duration ofclinical observation averaged 17 years and extended to over 30 years in eight patients. Their features have been correlated with those from reports of 48 comparable patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 67 publications
(25 reference statements)
0
26
0
2
Order By: Relevance
“…Today, presentation in adult life is rare since the lesion is usually diagnosed and closed surgically in infancy or early childhood. Marquis et al (12) reported that 804 patients with PDA were seen in Edinburgh and 37 of them reached the age of 50. Campbell found that 34% of PDA patients died before the age of 40 and 61% before the age of 60 (2).…”
Section: Discussionmentioning
confidence: 99%
“…Today, presentation in adult life is rare since the lesion is usually diagnosed and closed surgically in infancy or early childhood. Marquis et al (12) reported that 804 patients with PDA were seen in Edinburgh and 37 of them reached the age of 50. Campbell found that 34% of PDA patients died before the age of 40 and 61% before the age of 60 (2).…”
Section: Discussionmentioning
confidence: 99%
“…With a moderately sized PDA, sinus rhythm is usually present, although atrial fibrillation may occur in older individuals. 42 Left atrial enlargement may be present, and PR prolongation is found in 10% to 20% of patients. 43 The QRS axis is usually normal.…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%
“…Left ventricular volume overload may be characterized by deep S waves in V 1 and tall R waves in leads V 5 and V 6 , accompanied by nonspecific repolarization changes. 42,43 …”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%
“…(4) These usually involve relatively small left-to-right shunts that do not significantly overload the pulmonary vascular tree; hence, this subset of patients survive longer. (4,6,10) Fisher et al suggested that some patients may tolerate very high pulmonary arterial pressure for long periods without deterioration of their clinical status. (9) However, unrepaired PDA in these asymptomatic patients may eventually become clinically significant, particularly in conjunction with an acquired physiological insult from recurrent pneumonia, development of chronic obstructive pulmonary disease, ischaemic heart disease or calcific aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…(9) Calcification and atherosclerotic lesions make the ductus fragile and friable, increasing the technical difficulty of the surgical procedure. (3,10,14) Three-dimensional volume-rendered CT reconstruction allows for clear visualisation of the ductal morphology and demonstrates its spatial relationship to adjacent structures, including the aorta and pulmonary artery (Fig. 5).…”
Section: A 4b 4cmentioning
confidence: 99%